Microstructure and mechanical behavior assessment of Al–Cu composites fabricated through stir casting. (17th February 2018) - Madhusudan, S.; Sarcar, M. M. M.; Bhargava, N. R. M. R.
ABSTRACT: In this work, Al–Cu composite metallic materials are produced by dispersing copper particulates in an aluminum matrix using stir casting technique. In order to know the effect of reinforcement content, composites with varying weight fractions were fabricated. For comparison purpose, Al–Cu alloy is also fabricated and investigated. Increased densities have been observed with increasing particulate contents. Homogenization treatment has improved the hardness to a larger extent for both alloy and composites, particularly for rich composites. Composite with lean mixture of reinforcements has shown improvement in specific strength, whereas drop in specific strength has been observed for rich mixture of reinforcements. However, hardness is improved from 5% to 15% reinforcement content. Drop in strain has been observed for higher reinforcement composites. Response to cold upsetting is noticeable for lean composite which is on par with the alloy.